Hubungan Karakteristik Keluarga, Pengetahuan Dan Selfcare Pada Pola Makan Lansia Hipertensi - Pipit Festi W; Lusinta Dwi Kurniawati; Gita Marini (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
Hypertension is a disease that is risk for the elderly. The inability of the elderly to perform self care has an impact on health status. Self care in improper food management in the elderly with hypertension is the focus of attention to maintain the quality of life of the elderly. Family and elderly knowledge will be related to the implementation of self care elderly hypertension. This study aims to analyze the characteristics of the family (income, family assistance), knowledge and self care of the hypertension elderly diet at the medokan ayu community health center in surabaya.This research uses correlational analytic design with the cross sectional approach. The population in this study is the elderly hypertension at the medokan ayu community health center in surabaya. The sampling technique used was simple random sampling so as to obtain 44 elderly into the sample in this study. The independent variable is family characteristics (family income, and family assistance) as well as knowledge about eating patterns. The dependent variable is selfcare on a diet. Data were collected using a questionnaire sheet and then analyzed using the spearman rank and chi-square with a significant level <0.05. The results showed there was a relationship between family characteristics (income with a significance value of 0.04, family assistance with a significance value of 0.02, while the knowledge of the elderly with self care in the elderly hypertension diet significance value of 0.03. Elderly with hypertension requires assistance in self care.Keywords : family, knowledge, selfcare, elderly, hypertension